Will the climate of plant origins influence the chemical profiles of cuticular waxes on leaves of Leymus chinensis in a common garden experiment?. Issue 1 (17th December 2019) - Li, Yang; Hou, Xiangyang; Li, Xiaoting; Zhao, Xiao; Wu, Zinian; Xiao, Yu; Guo, Yanjun
Abstract: Cuticular wax covering the leaf surface plays important roles in protecting plants from biotic and abiotic stresses. Understanding the way in which plant leaf cuticles reflect their growing environment could give an insight into plant resilience to future climate change. Here, we analyzed the variations of cuticular waxes among 59 populations of Leymus chinensis in a common garden experiment, aiming to verify how environmental conditions influence the chemical profiles of cuticular waxes. In total, eight cuticular wax classes were identified, including fatty acids, aldehydes, primary alcohols, alkanes, secondary alcohols, ketones, β‐diketones, and alkylresorcinols, with β‐diketones the predominant compounds in all populations (averaged 67.36% across all populations). Great intraspecific trait variations (ITV) were observed for total wax coverage, wax compositions, and the relative abundance of homologues within each wax class. Cluster analysis based on wax characteristics could separate 59 populations into different clades. However, the populations could not be separated according to their original longitudes, latitudes, annual temperature, or annual precipitation. Redundancy analysis showed that latitude, arid index, and the precipitation from June to August were the most important parameters contributing to the variations of the amount of total wax coverage and wax composition and the relative abundance of wax classes. Pearson's correlation analysis further indicated that the relative abundance of wax classes, homologues in each wax class, and even isomers of certain compound differed in their responses to environmental factors. These results suggested that wax deposition patterns of L. chinensis populations formed during adaptations to their long‐term growing environments could inherit in their progenies and exhibit such inheritance even these progenies were exported to new environments. Abstract : We analyzed the variations of cuticular waxes among 59 populations of Leymus chinensis in a common garden experiment. Great intraspecific trait variations (ITV) were observed for total wax coverage, wax compositions and the relative abundance of homologues within each wax class. Our results suggested that wax deposition patterns of L. chinensis populations could inherit in their progenies.